ONGs, educação popular e protagonismo juvenil: um estudo da Associação Comunitária Nova Vida no município de Sapé-PB - Silva, Jeane Tranquelino da (2023)
The term NGO (Non Governmental Organization) was born in the 1940s. According to Ladim (1993), it was created by the UN (United Nations), at the end of World War II, to designate non-official entities that received financial aid from public bodies. to carry out projects of social interest. In Brazil, NGOs emerged between the 1950s and 1960s, gaining strength from the 1990s onwards, a period in which neoliberal governments encouraged the participation of civil society to act on social issues, favoring the ability to act in these institutions. This relationship favored the minimization of the State itself from the social sphere, and NGOs gained importance through structured partnership policies together with the public power. These entities operate in different areas and, despite their contradictions, generally collaborate with the development of citizenship and the expansion of democracy, also helping public management with the aim of minimizing the existing problems in the country. This thesis has the general objective of analising the NGO Associação Comunitária Nova Vida (ACNV) in order to explain whether it contribute to youth protagonism in struggles and social organizations in the municipality of Sapé-PB based on the principles of Popular Education. The specific objectives aim to: Identifying which principles of Popular Education are present in the NGO's actions; Systematize the contributions of the NGO that make possible the youth protagonism in the spaces of conquest by public policies; Analyze which methodological procedures are used in the NGO's actions; Analyze the impacts and achievements of youth protagonism promoted by the NGO on the young participants; Analyze the socioeconomic profile of the research subjects. Therefore, this research is anchored in authors such as: Freire (1996, 2001 and 2016), Gohn (2003, 2013 and 2014), Machado (2009 and 2012), Landim (1993) Calado (2016), Marx (2010) and in legislation that discusses NGOs, Youth Protagonism and Popular Education. Methodologically, we base ourselves on Dialectical Historical Materialism to better understand the contradictions in the field of NGOs, specifically the NGO ACNV in the context of social totality. This is an explanatory research with a case study based qualitative approach. As instruments for data collection, participant observation, document analysis, and semi-structured interviews with educators, students and the pedagogical coordination of the NGO ACNV were used. With regard to data analysis, we used the Content Analysis technique recommended by Bardin (2011). In general, the results revealed that the protagonism of adolescents and young people from the NGO Associação Comunitária Nova in spaces of participation in conquest and struggle for public policies, a contextualized education, as well as criticality and dialogue are some of the elements of popular education present in the ACNV NGO actions that contribute to the strengthening of youth protagonism in a popular education perspective. Therefore, this thesis argues that the NGO Associação Comunitária Nova Vida (ACNV) promotes youth protagonism in struggles and social organizations in the municipality of Sapé based on the principles of Popular Education